Madrasah Principal Leadership in Implementing the Motto "Amuntai the City of Fear" at Man 2 Amuntai, South Kalimantan Province - Suryana, Teddy; Husna, Nahdiyatul; Mas'amah, Siti; Afifah, Rasma; Yusuf, Yusuf; Andriana Gaffar, M. (International Journal of Educational Research & Social Sciences, 2022)
This study analyzes the leadership of the Madrasah Principal in implementing the motto Amuntai, the City of Fear at MAN 2 Amuntai. With the various challenges of the times and the explosion of information, madrasas are faced with being able to adapt to various changes that are so fast and result in changes to the learning system and curriculum that are applied. In the midst of this problem, the existence of madrasas in supporting local governments is shrinking. Through field research using a descriptive qualitative approach with transformational leadership indicators, this study proves that the leadership of the head of MAN 2 Amuntai in implementing the motto Amuntai Bertaqwa by taking the role of Idialized Influence, Individualized Consideration, Intellectual Stimulation.